Synthesis and characterization of NiCe based structured Ti02 nanocatalyst supports for green diesel production - YASIR, MADIHA (2017)
Diesel-like hydrocarbon fuel, obtained from vegetable oil, also known as 'Green Diesel' have emerged as an ideal alternate to petro-diesel with lesser emissions. However, the existing catalyst systems are not efficient enough to obtain higher yield and selectivity towards diesel range hydrocarbons.